Persepsi Mahasiswa Program Studi Pendidikan Geografi Universitas Tadulako Terhadap Pembelajaran Daring Ditengah Masa Pandemi Covid-19 - Fani, Sartika; Nisa, Zumrotin' (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2023)
The formulation of the problem in this study is how to implement teacher teaching methods during the new normal period in learning geography at SMA Negeri 6 Palu City. The study aimed to find out the implementation of teacher teaching methods during the new normal period in geography learning at SMA Negeri 6 Palu City. This type of qualitative research uses a descriptive approach. Data collection techniques using observation, interviews, and documentation. The data analysis techniques performed were data reduction, data presentation, and data verification. The results of the study show that in the implementation of learning in the new normal period, the methods used by teachers in teaching are more often lecture methods, questions and answers, and assignments when learning online (online) at home. In face-to-face learning at schools during the new normal period, teachers used to use group learning methods (project-based learning), lecture methods, questions and answers, discussions, demonstrations, and experiments. Learning in the new normal period is carried out simultaneously both face-to-face at school and online learning from home.